ژن له ڕوانگەی ڕیبازی ئيسماعیلى (ڕێبازی ئایینی ده‌وڵه‌تى فاطمى) - زەینەڵ, پ.د ئاراس فریق; احمد, دیمن حسیب (Sulaimani Journal for Humanities, 2023)
Women have a special place in the religion of the Fatimid state, which was set up to achieve such a state and then spread it, which is the Ismaili religion, which is a branch of the Shiite sect within the framework of the Islamic religion, where Shiites generally believe that Ali bin Abi Talib and his descendants (peace be upon them) are the most deserving of the caliphate. After the Prophet (may God bless him and grant him peace). The Ismailis were known as the Seven-Shiites, because they believed in the apparent imam, unlike the Shiites the (twelve imams). by (Maktoum) who believe in the return after death, as for the second class, they linked their imam to a chain link with a difference in the arrangement of their persons, and in their opinion, the imams are hidden or hidden, and they refrained from revealing them until the Ismaili movement reached their main goal, which is their arrival to political power, with the emergence of (The Imam) or the legitimate leader of that movement, Abdullah al-Mahdi, who was their first apparent imam and who established the Fatimid state in Morocco in (297 AH / 909 AD), and continued until the year (567 AH / 1171 AD), which occupied a large and vast geographical area, in which women formed an important part of it. Despite their great social responsibility in this religion, they did not give legitimacy to the administration of the state. Rather, their beliefs were harnessed for the benefit of the Imam, who was restricted to males rather than women, and they did not have a firm belief in women, and this is what is observed even in the one book. For the authors of books that doctrine.
Keywords: ژن ڕێبازی ئیسماعیلی دەوڵەتی فاطمی